Limits of the social-benefit motive among high-risk patients: a field experiment on influenza vaccination behaviour - Ozan Isler; Burcu Isler; Orestis Kopsacheilis; Eamonn Ferguson (BMC, 2020)
Abstract Background Influenza vaccine uptake remains low worldwide, inflicting substantial costs to public health. Messages promoting social welfare have been shown to increase vaccination intentions, and it has been recommended that health professionals communicate the socially beneficial aspects of vaccination. We provide the first test whether this prosocial vaccination hypothesis applies to actual vaccination behaviour of high-risk patients. Methods In a field experiment at a tertiary care public hospital in Istanbul, Turkey, we compare the effects of two motivational messages for promoting vaccination. Using a between-subjects single-blind experimental design patients were randomly assigned to frames emphasizing the vaccine's benefits to self (n = 125) or social benefits (n = 119). Free influenza vaccination was offered to each patient. Results Among 222 patients who were not vaccinated for the season prior to the study (72% medically assessed to be at high risk), 42% in the self-benefit frame chose to receive a vaccination compared with 34% in the social-benefits frame, but the difference was not statistically significant (aOR = 1.63, 95% CI 0.90 to 2.95, p = 0.108). Reasons for vaccination focused primarily on self-benefit (67%) rather than social-benefit (5%). Exploratory analysis showed that the effect of messages depended on patient perception of risk group membership (aORHigh / aORLow = 5.59, 95% CI 1.30 to 24.05, p = 0.021). In particular, emphasis on self-benefit was more influential among patients who perceived themselves to be in the risk group (aOR = 6.22, 95% CI 1.69 to 22.88, p = 0.006). Conclusions In contrast to the literature observing intentions of low-risk populations, we found no evidence that social-benefit motivates actual vaccination behaviour among a high-risk patient population. Instead, those who self-categorize as being in the high risk group are more motivated by the self-benefit message. Our results suggest that a stratified approach can improve coverage: even if an emphasis on social-benefit could be effective among low-risk groups, an emphasis on self-benefit holds more promise for increasing vaccination in medical organizational settings where high-risk groups are prevalent. Trial registration ClinicalTrials.gov NCT04230343 Retrospectively registered on the 13th January 2020.